An integrative approach to relationship marketing, customer value, and customer outcomes in the retail banking industry: a customer-based perspective from Turkey - Sayil, Emine Mediha; Akyol, Ayse; Simsek, Gulhayat Golbasi (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
Given how important it is to provide superior value to customers and to maintain customer loyalty for a sustainable competitive advantage, the aim of this paper is to examine the relationships among relationship marketing components of - trust, competency, commitment, communication, and conflict handling, - relationship investment, relationship quality, perceived customer value, satisfaction and loyalty in an integrated framework in the Turkish retail banking industry. Unlike previous studies, this research extends the literature by analysing affective as well as cognitive dimensions in the same model with a holistic view by simultaneously examining the direct and indirect effects of the related concepts. The distinctive nature of this study is its evaluation of customer satisfaction and loyalty from the perspective of actual consumers. The research model was tested using data collected from 685 retail banking customers by applying structural equation modelling. The findings show that relationship marketing induces loyalty through relationship quality, customer value, and satisfaction, which are mainly provided by trust, communication, and relationship investment. Furthermore, relationship investment and relationship quality are the most important factors in the development of customer value, satisfaction, and loyalty. The emotional value dimension, which captures the affective aspects of perceived value, has the strongest effect on both satisfaction and loyalty.
Keywords: Relationship marketing; relationship quality; perceived customer value; customer satisfaction; customer loyalty; PERCEIVED VALUE; SERVICE QUALITY; RELATIONSHIP MANAGEMENT; MEDIATING ROLE; VALUE CREATION; LOYALTY; SATISFACTION; TRUST; DETERMINANTS; Business & Economics